Inequality Issues and Their Effects on Social Relations in Society: A Philosophical Perspective - Orji, Chidi Paul (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025DO - 10.58709/niujhu.v10i1.2096, 2025)
Humanity is still plagued by inequality. In line with J. J. Rousseau, this article aims to investigate how social relationships in society have been impacted by existing inequality. The purpose of this paper is to show how inequality was the basis for human society's modernity, civilization, and political advancement. We argue that nature itself has produced inequality among humans since each person is born with their own unique set of potential. Despite this, we also argue that a number of measures, such as the creation of legislation and universal access to opportunities, should be taken by individuals to lessen these differences. As a result, the threat of inequality in our social relationships will change. Rousseau's theory of inequality will be discussed, with both its advantages and disadvantages noted. The subject of inequality is contextualized through the experience of Nigeria. This work's insightful analysis allows us to illustrate, within the framework of Rousseau's postulate, the tremendous threat that inequality has presented to our society. Keywords: Inequality, Social Relations, Rousseau, Corruption